Interaction between urban land expansion and land use policy: An analysis using the DPSIR framework. (December 2020) - Qu, Shijin; Hu, Shougeng; Li, Weidong; Wang, Hui; Zhang, Chuanrong; Li, Quanfeng
Highlights: The DPSIR framework is used to analyze the cause-effect relationship between urban land expansion and land use policy. Two abrupt change points in the process of urban land expansion correspond to the socioeconomic transitions in China. Negative effects have led to the implementation of some farmland protection and land-intensive use policy. Existing land-use policies show some weaknesses in controlling urban land expansion. Abstract: Many studies of urban land use have focused on understanding the process and drivers of urban land expansion (ULE). However, these studies rarely examined the long-term trends and abrupt change points of ULE. Moreover, the feedback loop between ULE and land use policy (LUP) has less been investigated. Thus, stakeholders sometimes experience difficulties when utilizing the existing ULE theories in urban land management practices and policy-making. In this study, we used the moving t -test method to detect the trend changes of urban land in China from 1981 to 2015 and a fixed-effects model to recognize the main drivers. The Driver-Pressure-State-Impact-Response (DPSIR) framework was applied to synthesize the existing knowledge of ULE to understand the interaction between LUP and ULE. Empirical analysis of 224 main cities indicated that China witnessed varying patterns of ULE through three different stages from 1981 to 2015. It revealed that the accelerated conversion of farmland to urban uses, along with inefficiency land use, led to a variety of farmland protection policies and intensive land use policies. In turn, however, these policies possibly affected the drivers of ULE. The impacts of drivers associated with land demand exhibited an increasing trend. Based on our findings, we suggest that land use policies should take the complexity and systematicity of ULE into consideration in urban land management. Overall, the framework, method, and findings of this study can help to increase the effectiveness of land use policy, not only in China but also in other developing countries.